Familial lysinuric protein intolerance presenting as coma in two adult siblings. Issue 5 (May 1989) - Shaw, P J; Dale, G; Bates, D
Abstract : Lysinuric protein intolerance (LPI) is an inborn error of metabolism which usually presents in infancy with failure to thrive and vomiting. Two patients are described who presented in adult life with hyperammonaemic coma due to LPI. Both had been underweight and had had intermittent gastrointestinal symptoms during childhood. They were of normal intellect and had maintained good health, until presentation in their thirties, by unconscious dietary protein avoidance. The diagnosis of LPI should be considered in patients who present with obscure relapsing coma associated with hyperammonaemia. Considerable clinical improvement may result from dietary protein restriction and citrulline supplementation.